Exploitation of Children in the Novels of Mulk Raj Anand: A Critical Examination of Social Exploitation in Mulk Raj Anand's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Mulk Raj Anand was one of the triumvirates who inaugurated the new section of writers of fiction along with R. K. Narayan and Raja Rao. Anand is a novelist of urgent social concerns and preoccupations, and the social impulse is at the heart of his writing. He is considered the Messiah of the downtrodden, the unwanted and the unloved. Even in a random reading of Anand‘s novels, the reader becomes immediately aware of such issues as the tyranny of the caste system, its injustice, and its social, moral and economic consequences, class conflicts, exploitation of various kinds of the poor by the rich, quest for identity, search for freedom etc. Under colonial rule, a number of social and economic changes took place and as a result of feudal society was gradually into a capitalist one. The class system in India has turned out to be a new kind of caste system. It is built on the cash nexus on which it thrives. It has created a society much more complicated and devious and in some respects more rigid than the one created by caste. Therefore, it has become a very powerful device force, for more damaging to social cohesion than caste, as it had tended to segregate people into the rich and the poor, the haves and the haves-not. (The International Journal of Engineering and Science)